Simulated density reorganization on the Weddell Sea continental shelf sensitive to atmospheric forcing - V. Teske; V. Teske; R. Timmermann; C. Nissen; C. Nissen; R. Zentek; R. Zentek; T. Semmler; T. Semmler; G. Heinemann (Ocean Science, 2025)
The strong Antarctic Slope Front in the southern Weddell Sea limits the present-day transport of modified Warm Deep Water (mWDW) onto the continental shelf and is associated with a characteristic V-shape in the density structure across the continental slope. The mechanisms controlling today's V-shape are well studied, but its future development is not yet well constrained. In this study, we run ocean model simulations for a 21st century Shared Socioeconomic Pathways (SSP) 3-7.0 emission scenario. The forcing is retrieved from atmospheric model output from simulations with a global climate model and from a higher-resolved regional atmospheric model respectively. We find that the resolution of the atmospheric model component influences the simulated future transport of mWDW onto the continental shelf into the Filchner Trough in the southern Weddell Sea through differences in the evolution of the depth and symmetry of the V-shape over the 21st century. In both simulations, reduced sea-ice formation and weakened Ekman downwelling reduce the depth of the V-shape and increase the sensitivity of its position above the slope to seasonal variations in sea-ice production and in the wind field. Using forcing data from an atmosphere model with higher resolution leads to an acceleration of the density redistribution on the continental shelf compared to the simulations forced with coarse-resolution data. This indicates that the SSP3-7.0 climate scenario may have a greater potential for a regime shift from a cold to a warm Filchner Trough through a cross-slope current before the end of the 21st century than suggested by other ocean simulations for the same scenario but with lower atmospheric resolution. As cross-slope currents disturb the continuity of the V-shape, we define a spatial grade of connectivity to quantify the lateral integrity of the V-shape along the continental slope. We find that the integrity of the V-shape reduces with a delay of 3 months after a strong cross-slope current of mWDW enters Filchner Trough. Atmospheric downscaling increases the potential for a regime shift, dominated by warmer summer air temperatures. The Antarctic Slope Front is temporarily disturbed by cross-slope currents but the primary reason for the regime shift is the cross-slope density gradient.